Relation between Serum Intact Parathyroid Hormone Level and Hematocrit in Chronic Kidney Disease Patients - Adhikary, L.P.; Pokhrel, A.; Yadava, S.K.; Khadka, D.; Thakur, R. (Kathmandu University Medical Journal, 2017)
Background Anemia is a common complication of chronic kidney disease. There are various causes of anemia in chronic kidney disease patients on hemodialysis. Secondary hyperparathyroidism is one of the less recognized causes of anemia in chronic kidney disease patients.Objectives The main objective of the study is to find the correlation between intact parathyroid hormone and hematocrit level in chronic kidney disease (CKD) patients undergoing hemodialysis.Method Verbal consent was taken from all the participants. Eighty participants between the age of 29 and 70 years with chronic kidney disease having indication of hemodialysis were included in this study. Hematocrit was measured by bioelectrical impedance method and serum intact parathyroid hormone was by using Chemi Luminescence Immuno Assay (CLIA) method.Result A weak reverse correlation was found between serum intact parathyroid level and hematocrit (r= -0.33).Conclusion In chronic kidney disease patient, there is reverse correlation between level of serum intact parathyroid and hematocrit level. This association may have clinical relevance in assessing the cause of unexplained low hemoglobin level in CKD patients.